Akumulasi Metode Monte Carlo dalam Memperkirakan Tingkat Penjualan Keripik Sanjai - Aldo Eko Syaputra (Jurnal Informatika Ekonomi Bisnis, 2023)
Sanjai chips are one of the typical snacks of West Sumatra which are sold by tek gadih shops, increased sales on certain days and months make employees overwhelmed dealing with buyers, causing buyers to not be served evenly, and increased purchases make available sanjai stocks run low or run out. and resulted in sales being not optimal, therefore it is necessary to conduct a study to predict sales in the future. So that the availability of sanjai chips in the warehouse can be increased so that service is guaranteed and sales are optimal. The method chosen in this research is the Monte Carlo Method by processing data on the number of sales from 2020, 2021, and 2022. The results of this study are that it can predict the number of sales of sanjai chips at Tek Gadi stores in the following year with an average level of accuracy. 83%, in 2022 with an average sales of 1,746, and 91% with an average sales of 1,701 in 2021. So that this research can be used as reference material by sanjai tek gadih in making decisions to increase sales in the future.